THE EFFECT OF MASSAGE ON SOME RECOVERY PARAMETERS - Bilgehan Baydil; Veli Volkan Gürses; Mustafa Can Koç (ümit doğan üstün, 2017)
The aim of this study was investigate the effect of total classic body massage on some recovery and circulation parameters. Fourteen non-athlete physically active male university students voluntarily participated in the study. Participants randomly divided into two group Massage Group (MG) and Control Group (KG). All participants were informed about the purpose of the study, food consumption and not join the exercise before the test. 30 second Wingate Test protocol was used as exhaustive exercise. Heart Rate (KAH), systolic (SKB) and diastolic (DKB) blood pressures and blood lactate measured immediately after and 15 min recovery after exhaustive exercise. During 15 min recovery, total classic body massage was applied to MG group. Passive recovery was applied to KG group. The Shapiro Wilk Test of normality was used to determine if the data were normally distributed. Pair Sample T-Test was used for data's were normally distributed, Wilcoxon Signed Ranks Test was used for data's were not normally distributed. All analyses were set at p.05). Both groups blood lactate levels were significantly decreased (MG; t = 4.47, p = .004; KG; t = -2.36, p = .018). Blood lactate levels were determined as -51.60% and -24.63% on MG group and KG group respectively. Consequently, the total classic body massage thought to be effective on lactate removal level in short period of recovery.